Descriptive epidemiological study of vaginal cancer using data from the Osaka Japan population-based cancer registry: Long-term analysis from a clinical viewpoint. Issue 32 (August 2017) - Yagi, Asami; Ueda, Yutaka; Kakuda, Mamoru; Tanaka, Yusuke; Egawa-Takata, Tomomi; Morimoto, Akiko; Iwamiya, Tadashi; Matsuzaki, Shinya; Kobayashi, Eiji; Yoshino, Kiyoshi; Fukui, Keisuke; Ito, Yuri; et al.
Abstract : Abstract: Vaginal cancer is such a rare tumor that epidemiological and clinical information for it is based mainly on studies of small numbers of cases. The aim of the present study was to perform a descriptive epidemiological analysis of vaginal cancer using a significantly larger population-based dataset from the Japanese Osaka Cancer Registry. The age-standardized incidence of vaginal cancer per 1, 000, 000 persons, from 1976 to 2010, was calculated and examined for trends. Relative-survival analysis was applied to estimate a more up-to-date 10-year period calculation, using data from recently followed-up patients. The conditional 5-year survival of patients who survived for 0 to 5 years after diagnosis was calculated. A total of 481 cases of vaginal cancer were registered in Osaka during the 35-year period from 1976 to 2010. The age-adjusted incidence rate has significantly and consistently decreased over this time [annual percent change (APC) = −1.29, 95% confidence interval (95% CI): −0.3 ∼ −2.2]; however, due to significant population aging, the raw incidence of vaginal cancer appeared to have been increasing. The 10-year relative survival of patients with surgery-based treatments was comparable to that of radiation-based treatments, implying that surgery and radiotherapy provide similar therapeutic benefits ( P = .98). The 10-year relative survival was not significantly different during the period of 1976 to 2000 compared with the period of 2001 to 2008, although there has been, in the latter period, a tendency for improvement of long-term survival, especially for survival longer than 5 years. The longer the time after diagnosis, the higher the conditional 5-year relative-survival at 0 to 4 years after diagnosis. The age-adjusted incidence of vaginal cancer has decreased since 1976. Regrettably, the 10-year survival rate did not similarly improve, and it remained stable during the period from 2001 to 2008, compared with the period from 1976 to 2000, indicating that significant work remains to be done to develop more effective vaginal cancer treatments.